(untitled) (Journal of the College of Basic Education, 2023)
The objective of the current research is to identify the level of possession of students (the second stage - Mathematics Department / College of Basic Education - Al-Mustansiriya University) (for deep understanding skills and its relationship to their ability to solve mathematical problems), in order to achieve the goal, the researchers used the descriptive approach and two tests were prepared in order to measure skills Deep understanding consisted of (20) paragraphs distributed on deep understanding skills, which are: include (generative thinking, developing scientific explanations, decision making, and asking questions). And a test to measure the ability of students to solve the mathematical problem, which consisted of (20) items distributed on the skills of solving the mathematical problem (the skill of understanding the problem, the skill of planning the solution, the skill of implementing the solution, the skill of verifying the validity of the solution). (0.88) for deep understanding skills and (0.83) To solve the mathematical problem, and after applying the test to the sample consisting of (100) male and female students from the second stage students - Mathematics Department - College of Basic Education and statistical data processing, the two researchers reached the following results: 1- The students of the second stage possess deep understanding skills to a good degree. 2- The students of the second stage have the ability to solve the mathematical problem with a good degree. 3- There is a positive direct relationship between deep understanding skills and the ability to solve mathematical problems.